On the Emergence of the Concept of “Linguistic Rights” in Brazilian Legal Doctrine - Santa Rosa Matos, Marcos Paulo; Garcia Costa Carvalho, Maria Leônia (Íkala, Revista de Lenguaje y Cultura, 2024)
This paper analyzes the development of the concept of “linguistic rights” in Brazilian legal discourse, highlighting its theoretical evolution, political advocacy and incorporation into national legislation, based on the notion of “archive” proposed by the French school of discourse analysis. The text is structured in three parts: firstly, it looks at the contribution of Francisco Gomes de Matos, whose lists of rights and calls for recognition were crucial to the theoretical discussion and political mobilization in favor of these rights, especially in the international context. Next, the assimilation of language rights into Brazilian legal norms is examined, with emphasis on the protection of minority communities (deaf people, indigenous people, quilombolas, descendants of immigrants and foreigners) and the importance of the 1988 Constitution in this process. Finally, we discuss the proposal for a general legal discipline for language rights, represented by Bill 489/2019, which could constitute a significant framework for their protection in the country. The analysis shows the complexity and challenges in making language rights effective in Brazil, while recognizing the rich memory of struggles and advances that support this cause.